Sodium-23 magnetic resonance imaging during and after transient cerebral ischemia: multinuclear stroke protocols for double-tuned (23)Na/(1)H resonator systems - Wetterling, Friedrich (My University, 2012)
A double-tuned 23Na/1H resonator system was developed to record multinuclear MR image data during and after transient cerebral ischemia. 1H-diffusion-, 1H perfusion, 1H T2-, 1H arterial blood flow- and 23Na spin density-weighted images were then acquired at three time points in a rodent stroke model: (I) during 90 min artery occlusion, (II) directly after arterial reperfusion and (III) one day after arterial reperfusion. Normal 23Na was detected in hypoperfused stroke tissue which exhibited a low 1H apparent diffusion coefficient (ADC) and no changes in 1H T2 relaxation time during transient ischemia, while 23Na increased and ADC values recovered to normal values directly after arterial reperfusion. For the first time, a similar imaging protocol was set-up on a clinical 3T MRI site in conjunction with a commercial double-tuned 1H/23Na birdcage resonator avoiding a time-consuming exchange of resonators or MRI systems. Multinuclear 23Na/1H MRI data sets were obtained from one stroke patient during both the acute and non-acute stroke phases with an aquisition time of 22 min. The lesion exhibiting low ADC was found to be larger compared to the lesion with high 23Na at 9 h after symptom onset. It is hoped that the presented pilot data demonstrate that fast multinuclear 23Na/1H MRI preclinical and clinical protocols can enable a better understanding of how temporal and regional MRI parameter changes link to pathophysiological variations in ischemic stroke tissue.
PUBLISHED
Keywords: Neuroscience; Next Generation Medical Devices